2020
DOI: 10.3390/ijerph17124531
|View full text |Cite
|
Sign up to set email alerts
|

Regional Heterogeneity of Application and Effect of Telemedicine in the Primary Care Centres in Rural China

Abstract: The increasing concerns of the geographical maldistribution of medical resources have sparked worldwide interests in exploring the potential of telemedicine in the rural health system. This study aimed to investigate the application and effect of telemedicine as well as their regional heterogeneity in the primary care centres in rural China. Based on the stratified multistage cluster sampling, a cross-sectional study was conducted among 358 township health centres (THCs) from eastern, central and western China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Township health centers, as primary care facilities that provide inpatient services, presented higher probability of PPH (22.6%) than county hospitals (7.93%). The result may be due to clinical uncertainty given the relatively lower staff capacity ( 36 ) or could be physician-induced demand as a result of a lower bed occupancy rate and economic incentives at primary care facilities ( 22 , 37 ). Patients usually bypass primary care facilities to seek health care in hospitals in China ( 21 ); therefore, lack of primary care services might be a key reason for PPHs at county hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Township health centers, as primary care facilities that provide inpatient services, presented higher probability of PPH (22.6%) than county hospitals (7.93%). The result may be due to clinical uncertainty given the relatively lower staff capacity ( 36 ) or could be physician-induced demand as a result of a lower bed occupancy rate and economic incentives at primary care facilities ( 22 , 37 ). Patients usually bypass primary care facilities to seek health care in hospitals in China ( 21 ); therefore, lack of primary care services might be a key reason for PPHs at county hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al found that 58.66% of the township health centers in rural China applied telemedicine in 2017, and this proportion was much higher in western China, with the central region following and the lowest in the eastern region. In each region, the prevalence of telemedicine adoption also tended to be higher in the less developed province (34). During COVID-19 pandemic, it was reported that continuity of care for patients with rheumatic disease could be guaranteed through telemedicine, mainly through telephone consultations, while adoption of other forms of telemedicine, such as asynchronous communication and video consultations was still low in the Netherlands (35).…”
Section: Telemedicine Around the Worldmentioning
confidence: 99%
“…More specific health services are increasingly available in rural areas with telemedicine (8). Telemedicine improves patient satisfaction, especially in pediatric and rehabilitation services (9).…”
Section: Positive Impactmentioning
confidence: 99%
“…Private telemedicine network service companies, Non-Governmental Organizations (NGOs), and the government want a reasonable price to cover the costs of providing telemedicine (13). Health insurers need to estimate cost coverage for their clients by using telemedicine services (9). All research journals do not explain the standard of validity of informed consent in telemedicine that can be used as a reference in obtaining it (oral or e-form).…”
Section: A Telemedicine Policies or Standardsmentioning
confidence: 99%